2018
DOI: 10.1038/s41598-017-18532-2
|View full text |Cite|
|
Sign up to set email alerts
|

Surveillance of vector-borne pathogens under imperfect detection: lessons from Chagas disease risk (mis)measurement

Abstract: Vector-borne pathogens threaten human health worldwide. Despite their critical role in disease prevention, routine surveillance systems often rely on low-complexity pathogen detection tests of uncertain accuracy. In Chagas disease surveillance, optical microscopy (OM) is routinely used for detecting Trypanosoma cruzi in its vectors. Here, we use replicate T. cruzi detection data and hierarchical site-occupancy models to assess the reliability of OM-based T. cruzi surveillance while explicitly accounting for fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…We identified triatomines using dichotomic keys (Lent & Wygodzinsky, ). We examined the faeces of the collected triatomines by optical microscopy according to Minuzzi‐Souza et al (); fresh (400x) and Giemsa 10%‐stained (1000x) hindgut contents were examined to detect T. cruzi (Cuba Cuba, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified triatomines using dichotomic keys (Lent & Wygodzinsky, ). We examined the faeces of the collected triatomines by optical microscopy according to Minuzzi‐Souza et al (); fresh (400x) and Giemsa 10%‐stained (1000x) hindgut contents were examined to detect T. cruzi (Cuba Cuba, ).…”
Section: Methodsmentioning
confidence: 99%
“…We extracted DNA from blood samples (300 μl) according to the recommendations of the Biopur DNA Extraction Kit (Biometrix). We extracted DNA from triatomines (intestinal tissues) and sandflies (female thoraces and proximal abdominal segments) with the Illustra Tissue and Cells Genomic kit (GE Healthcare), according to Minuzzi‐Souza et al () and Machado et al (), respectively. We quantified DNA samples with the NanoVue™ Plus Spectrophotometer (GE Healthcare) using the wavelength 220–330 nm; the data were expressed in ng/μL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low percentage of domiciliary infestations found in this work is probably not only due to a few vulnerable houses recorded in the study area, but also due to the low sensitivity of the manual method used for searching for triatomines (hour-man technique). Previous investigations of routine surveillance systems used in the context of detecting vector-borne diseases like Chagas, have shown that these systems have sensitivity estimates frequently below 50%, likely resulting in underestimates in the real infestation vector numbers 36,37 . Historically, the house has been considered a risk factor, especially those houses whose structure offers suitable refuge for triatomines.…”
Section: Discussionmentioning
confidence: 99%